1997
DOI: 10.1074/jbc.272.43.26803
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Factor 1 Represses Ras-induced Transcriptional Activation of the c-fos Gene

Abstract: Heat shock factor 1, the critical molecular regulator of the stress response is conserved throughout eukaryotic organisms and activates the transcription of heat shock genes. We now show that heat shock factor 1 inhibits the expression of c-fos, an immediate early gene that controls responses to extracellular stimuli for growth and differentiation. Heat shock factor 1 inhibits the transcription of the c-fos gene and antagonizes the activating effects of the signal transducing protein Ras on the c-fos promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 35 publications
0
95
0
Order By: Relevance
“…4), and pretreatment of the oxLDLsup with blocking antibodies against HSP70 inhibited this increase. The increased IL-1β concentrations was also reduced when using oxLDLsup from macrophages transfected with a plasmid expressing mutated HSF1 (pHSF1mut) that inhibits HSP production [8] (Fig. 4).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…4), and pretreatment of the oxLDLsup with blocking antibodies against HSP70 inhibited this increase. The increased IL-1β concentrations was also reduced when using oxLDLsup from macrophages transfected with a plasmid expressing mutated HSF1 (pHSF1mut) that inhibits HSP production [8] (Fig. 4).…”
Section: Resultsmentioning
confidence: 94%
“…Human macrophages were transiently transfected with a plasmid expressing dominant negative heat shock factor-1 (HSF1) that inhibits the formation of active HSF1 homotrimers (HSF1mut) [8] essentially as previously described [9]. In brief, empty plasmids (25 μg) or HSF1mut plasmids (25 μg) were mixed with 50 μg N- [1-(2,3-dioleoyloxypropyl]-N,N,N,-trimethylammonium methylsulfate (DOTAP) in 500 mL OptiMEM (Roche, Mannheim, Germany) and incubated at room temperature for 20 min before addition to the cultured macrophages for 2.5 h. After 24 h the macrophages were then treated with 50 μg/mL oxLDL or control medium without oxLDL for 24 h at 37°C.…”
Section: Mutated Hsp1 Expression Plasmidmentioning
confidence: 99%
“…53,54 In addition, HSF1 can also act as a negative regulator of certain non-heat shock genes, including interleukin (IL)-1b or TNFa. [55][56][57] Myers et al 52 had shown that in heat-shocked somatic cells at least two promoters of putative apoptosisrelated genes -TNFRSF member 21 and death domain DNAbinding protein 2 -bound to and were activated by HSF1. Here we have aimed to disclose apoptosis-related genes that are regulated by HSF1 in spermatogenic cells.…”
Section: Discussionmentioning
confidence: 99%
“…In both panels, color-coding goes from red (upregulation) to green (downregulation), with yellow being no change and purple being not identified. Known transcriptional downstream targets of the Ras pathway, such as genes encoding c-Fos, cyclin D1 and p21 Cip1 (Albanese et al, 1995;Chen et al, 1997;Kivinen et al, 1999;Nheu et al, 2004), were upregulated in the transformed cell line and downregulated in reverted cell lines, and have been scored as an internal control of reliability for our results. Other cell cycle-related genes showing the same behavior (i.e.…”
Section: Ros Production and Cell Death In Normal Transformed And Revmentioning
confidence: 99%